An H-NS Family Protein, Sfh, Regulates Acid Resistance by Inhibition of Glutamate Decarboxylase Expression in Shigella flexneri 2457T - Niu, Chang; Wang, Dongshu; Liu, Xiaoqing; Liu, Hongsheng; Liu, Xiankai; Feng, Erling; Pan, Chao; Wang, Ruifeng; Xiao, Wei; Liu, Xingming; Liu, Xinrui; Zhu, Li; et al. (Frontiers in Microbiology, 2017)
The glutamate-dependent acid-resistance system is the most effective acid tolerance pathway in Shigella, allowing survival in extremely acidic environments. However, the regulation of this system in Shigella remains elusive. In the current study, we identified significant differences in the levels of glutamate decarboxylase between three Shigella flexneri strains with different levels of acid resistance using blue native-polyacrylamide gel electrophoresis (PAGE) and isoelectric focusing/sodium dodecyl sulfate (SDS)-PAGE analysis. The results showed that the degree of acid resistance and the levels of GadA/B were significantly lower in strain 2457T compared with two other S. flexneri strains. It has been reported that plasmid pSf-R27 is expressed in strain 2457T but not in the other 142 sequenced S. flexneri isolates. pSf-R27 encodes protein Sfh, which belongs to a family of histone-like nucleoid-structuring proteins that participate in the transcriptional control of glutamate-dependent acid resistance, implicating pSf-R27 in the lower acid resistance of strain 2457T. Transformation of pSf-R27 or sfh alone into strain 301 resulted in decreased expression of GadA/B in the recombinant strains. Thus, we confirmed that H-NS family protein Sfh, bound to the gadA/B regulatory region and regulates the expression of glutamate decarboxylase at the transcriptional level. We also examined the acid tolerance of the wild-type and recombinant strains using flow cytometry and determined that the acid tolerance of S. flexneri is closely related to the expression of GadA/B. These findings further our understanding of the acid tolerance of S. flexneri, especially via the glutamate-dependent pathway.